Wagner, Schumann, and the Lessons of Beethoven's Ninth - Reynolds, Christopher A. (Book collections on Project MUSE., 2015)
"Reynolds shows that the stylistic advances made by Richard Wagner and Robert Schumann in 1845-46 stemmed from a deepened understanding of Beethoven's techniques and strategies in the Ninth Symphony, particularly the use of counterpoint involving contrary motion. The trail of influences that Reynolds explores extends back to the music of Bach and ahead to Tristan and Isolde, as well as to Brahms's First Symphony."--Provided by publisher.